De jonge Vlaamse Schilderkunst. (Antwerpen : Harmonie, 1958)
Aerts, Ernest ; Battaille, Irène ; Bergen, Emiel ; Bierwerts, Willem ; Bogaert, Andr& ; Burssens, Jan ; Cobbaert, Jan ; Cox, Pierre ; De Vogelaere, Fons ; De Leeuw, Bert ; Estervam, Vic ; Godderis, Jack ; Haenen, Toon ; Humblet, Theo ; Leblanc, Walter ; Mara, Pol ; Meerbergen, Rudolf ; Mommaerts, Geo ; Peire, Luc ; Segers, Maria ; Smolders, Paul ; Swimberghe, Gilbert ; Van Elzen, Staf ; Van Gijsegem, Paul ; Van Hoeydonck, Paul ; Verheyen, Jef, etc.
De jonge Vlaamse Schilderkunst, Harmonie, Antwerpen, 10-V tot 8-VI - 58
boek
Keywords: Vlaanderen